Faktor Pendukung Terbentuknya Jaringan Perdagangan antar Kesultanan di Nusantara - Budi Sulistiono (Buletin Al-Turas, 2011)
The emergence of Islamic kingdoms/sultanates in the Nusantara (Indonesian archipelag), suchas SamuderPasai, Demak, Banten, Cirebon, MAtaram, Tidore, Gowa Tallo, and others are evidence that iIslam was accepted and spread throughout the Nusantara. The function of the former capital cities of Islamic kingdoms in the archipelago were to be maintained as trade center and the center of political power. In the end the cities changed into centers of educational activities with the emergence of traditional and modern institutions many religious sciences with various levels were studied  and gave birth to many prominent scholars who later became role models in their respective regions.